2011
DOI: 10.1007/s10450-011-9358-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoscale curvature sign and bundle structure on supercritical H2 and CH4 adsorptivity of single wall carbon nanotube

Abstract: The adsorptivities of supercritical CH4 and H2 of the external and internal tube walls of single wall carbon nanotube (SWCNT) were determined. The internal tube wall of the negative curvature showed the higher adsorptivities for supercritical CH4 and H2 than the external tube wall of the positive curvature due to their interaction potential difference. Fine SWCNT bundles were prepared by the capillary force-aided drying treatment using toluene or methanol in order to produce the interstitial pore spaces having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Aiming to reach the objective of 180 v/v, several research groups worldwide have tried to develop different classes of porous materials over the past two decades. These materials include Amberlite, dow resins, zeolites, silica-based compounds, xerogels, aerogels, MCM41, and carbon-based materials such as superactivated carbons, single-walled carbon nanotubes (SWCNTs), activated carbon fibers, and carbon nanohorns. ,, Conventional zeolites typically exhibit very low storage capacities not exceeding 100 v/v, which are far from the DOE targets. , Attempts to increase their low storage capacities have been hindered by their structural limitations such as the presence of cylindrical mesopores and difficulties in practically reaching surface areas greater than 1000 m 2 /g. , The grand canonical Monte Carlo (GCMC) simulation results of Cracknell et al confirmed that, for the adsorptive storage of natural gas, a microporous carbon that has an optimal pore size is better than an optimal zeolite. They found that, at 3.4 MPa and 274 K, a prototype carbon with slit-shaped micropores yields a theoretical storage capacity of 166 g/L compared to 53.1 g/L for a zeolite with cylindrical pores of the same dimensions.…”
Section: Adsorbed Natural Gas (Ang)mentioning
confidence: 99%
“…Aiming to reach the objective of 180 v/v, several research groups worldwide have tried to develop different classes of porous materials over the past two decades. These materials include Amberlite, dow resins, zeolites, silica-based compounds, xerogels, aerogels, MCM41, and carbon-based materials such as superactivated carbons, single-walled carbon nanotubes (SWCNTs), activated carbon fibers, and carbon nanohorns. ,, Conventional zeolites typically exhibit very low storage capacities not exceeding 100 v/v, which are far from the DOE targets. , Attempts to increase their low storage capacities have been hindered by their structural limitations such as the presence of cylindrical mesopores and difficulties in practically reaching surface areas greater than 1000 m 2 /g. , The grand canonical Monte Carlo (GCMC) simulation results of Cracknell et al confirmed that, for the adsorptive storage of natural gas, a microporous carbon that has an optimal pore size is better than an optimal zeolite. They found that, at 3.4 MPa and 274 K, a prototype carbon with slit-shaped micropores yields a theoretical storage capacity of 166 g/L compared to 53.1 g/L for a zeolite with cylindrical pores of the same dimensions.…”
Section: Adsorbed Natural Gas (Ang)mentioning
confidence: 99%
“…We integrated the pairwise FH effective potential to calculate the quantum H 2 – or D 2 –SWCNT interaction potential. The detailed calculation procedures are given in other papers. , …”
Section: Experimental and Simulation Proceduresmentioning
confidence: 99%
“…5 Especially, specic nanospaces in the CNT bundles, such as interstitial channels and external grooves, have signicant interactions with aromatic 6 and gas molecules, such as Ar, 7 Ne, 8 He, 8,9 CF 4 , 10 H 2 , 11 N 2 , 12,13 O 2 , 13 and C n H 2n+2 , 14,15 and also exhibit selectivity for molecules. 6,16,17 However, the rather low gas selectivity and storage capacity on the p-conjugated surfaces of the CNTs has limited their applications to gas sensors and separations. In order to improve such a drawback, covalent 18 and non-covalent functionalization 19,20 and coating by inorganic materials 21 have been carried out.…”
Section: Introductionmentioning
confidence: 99%